Improving telmisartan mechanical properties through the formation of telmisartan and oxalic acid co-crystal by slow evaporation and ultrasound assisted co-crystallization from solution methods - Hestiary Ratih; Jessie Sofia Pamudji; Fikri Alatas; Sundani Nurono Soewandhi (Songklanakarin Journal of Science and Technology (SJST), 2020)
Telmisartan (TMS) is used for the prevention and treatment of hypertension. However, it has poor mechanical properties. The purpose of this research was to improve the mechanical properties of TMS through the formation of co-crystal TMS with oxalic acid (OXA) and to compare the mechanical properties of TMS-OXA 1:1 co-crystal obtained from the different co-crystallization techniques. Co-crystals were prepared by the slow evaporation (SE) and ultrasound assisted co-crystallization from solution (USSC) methods. The tabletability profiles were plotted between compaction forces in the range of 4.98‒29.89 kN vs. tensile strength. The tablet tensile strength of TMS in compaction force >14.98 kN had severe capping or lamination. In contrast, the tablet tensile strengths of the TMS-OXA SE and USSC co-crystals were higher and could be easily formed into tablets in all of the compaction forces. It can be concluded that the TMS-OXA co-crystals prepared by the SE and USSC methods have improved mechanical properties of the telmisartan tablet.